The Validity of Notarial Authentic Deeds Prepared Through Service Bureaus in the Perspective of the Notary Code of Ethics - Marlyn Christ Nathasia Br Sumbayak; Rasji Rasji (Jurnal Daulat Hukum, 2025)
This study aims to analyze the validity of notarial authentic deeds prepared through cooperation with service bureaus and to examine violations of the Notary Code of Ethics within such practices. This collaborative phenomenon raises legal and ethical issues, as it potentially disregards the formal requirements for deed formation as stipulated in Article 15 and Article 16 paragraph (1)(m) of Law No. 2 of 2014 concerning the Office of the Notary (UUJN), as well as Article 1868 of the Indonesian Civil Code. This research employs a normative juridical method with statutory, conceptual, and case approaches, and examines practices in the Central Jakarta area as an illustration of the application of these norms. The findings indicate that deeds drafted through service bureaus lose their authenticity and possess only the evidentiary value of private deeds. From an ethical perspective, such cooperation violates Article 4(g) of the Notary Code of Ethics, which prohibits the use of intermediaries to obtain clients.